Downtown or Suburbs – How the Location in the Urban Agglomeration Zones Affects the Price of Flats? - Izabela RĄCKA; Ivo KOSTOV (Communications of International Proceedings, 2021)
Today’s cities have been developing for hundreds years, however they have already existed in antiquity. Development of cities is related to an increase of population and the territorial expansion. When looking for a suitable location for a residential investment, an inversot is guided by many factors: investment availability, efficiency, attractiveness, accessibility, quality of surroundings etc. The aim of the study was to verify empirically a dependency of location in the agglomeration on housing prices. The research covered the housing market in two CCE cities (Kalisz, PL and Varna, BG) in years 2019–2020. We identified the location of each property in one of three agglomeration zones: downtown, city beyond downtown and suburbs. First, we compared two samples to check if it is feasible that they came from the same population. Then, data was subjected to regression analysis. The analysis of data allowed us to conclude that location in each of three agglomeration zones does affect the prices of flats. It turned out that depending on the type of city, prices went up or down due to the distance from downtown, which is not only a contribution to the development of science, but also information that could be used by developers or property valuers to establish prices of flats, as well as city managers to set up prices of unbuilt lots.
Keywords: Housing market; market analysis; suburbanization